Gendered Career Choices: Paths Toward Studying a Degree in Physical Activity and Sport Science - Serra, Pedrona; Soler, Susanna; Camacho-Miñano, María José; Rey-Cao, Ana; Vilanova, Anna (Frontiers in Psychology, 2019)
Drawing on social cognitive career theory (SCCT), we examined factors affecting interest in pursuing a degree in physical activity and sport science (PASS) among Spanish teenage students. Although women were awarded 55.1% of all bachelor degrees in Spain in 2017-2018, female enrolment in PASS degrees is decreasing and currently stands below 20% across the country. To better understand the under-representation of women in this field, 4146 students (50.2% girls; mean age=16.82 years; SD=.837) participated in a survey designed to measure a series of SCCT constructs: interest in studying a PASS degree, career outcome expectations and goal representations, and perceived social supports. With these data, we tested a set of path analysis models to explain gender differences in interest in studying a degree in PASS. These models tested the assumption that interest in PASS would mediate the paths from outcome expectations and social supports to goal representations. Model 1 assumed that interest would partially mediate the path from outcome expectations to goal representations, Model 2 assumed complete mediation, and Model 3 assumed absence of mediation. All models were tested separately for boys and girls. Our results provide information on how male and female students set personal goals based on expected career outcomes and show that this process is affected by gender stereotypes. The lack of interest by young women in studying a degree in PASS (only 7.8% of girls expressed this interest compared with 19.0% of boys), together with the gender differences observed in perceived social supports, outcome expectations, and goal representations, have several important theoretical and practical implications. The present research suggests that interventions that foster positive outcome expectations and social support are necessary to increase interest in studying PASS among teenage girls.